2008
DOI: 10.1097/bsd.0b013e318074dded
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Predictors of Residual Low Back Pain After Laminectomy for Lumbar Spinal Canal Stenosis

Abstract: Our results indicate that preoperative lordosis angle and lumbar ROM were the significant radiographic predictors for residual LBP after laminectomy for LCS. Patient with flatback and limited lumbar mobility before surgery are prone to suffer residual LBP. It is suggested that these sagittal radiographic parameters should be taken into account when choosing laminectomy as the surgical option for LCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Of 18 studies, three failed to produce the data needed for the meta-synthesis [27][28][29]. Thus, the quantitative meta-analysis was performed on 15 studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. LSS had been used as an inclusion criterion in 15 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of 18 studies, three failed to produce the data needed for the meta-synthesis [27][28][29]. Thus, the quantitative meta-analysis was performed on 15 studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. LSS had been used as an inclusion criterion in 15 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Wide decompression leads to a greater incidence of postoperative instability, progressive stenosis, and recurrence of LBP or leg symptoms [25-27]. Biomechanical studies have also reported a positive correlation between the extent of decompression and instability [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since many authors reported long term deterioration of surgical outcomes, relatively shorter term outcome reports may have some demerit in acceptance as generalized scientific data 2,9,35,44,52,62) . The overall successful outcomes of surgical treatments for lumbar spinal stenosis, based on retrospective studies with more than 4-year follow up, were 23.8-91% according to various outcome assessment tools (Table 2) 1,11,12,14,21,22,25,26,34,36,[50][51][52]56,61) . In 1997, Airaksinen et al studied 438 patients with lumbar spinal stenosis and average 4.6-year follow up period after surgery and noted a good to excellent outcome in 62% of the patients 1) .…”
Section: Long-term Surgical Outcomesmentioning
confidence: 99%
“…Another studies did not find associated spondyolisthesis in lumbar spinal stenosis as a prognostic factor 25,56) . Some authors postulated decreasing preoperative lumbar lordosis angle and lumbar range of motion, more than 10 degrees of sagittal rotation angle, more than 50 degrees of facet angle, disc height over 6.5 mm, and motion at the spondylolisthetic level more than 1.25 mm as unfavorable prognostic factors 10,28,61) .…”
Section: Radiologic Factorsmentioning
confidence: 99%
See 1 more Smart Citation